Variations of the platelet aggregation during the cycle of menstruation (Revista Española de Fisiología, 1971)
The platelet aggregation during the menstrual cycle has been studied. They have found a significant decrease of the aggregation on the 13th-14th days of the mens trual cycle.The significant of the preliminary results are briefly discussed.